The contribution of the Philosophy of Education in the teaching of Humanities in the University of Costa Rica - Rangel Díaz, Gabriela (2019)
The teaching of Humanities can be traced back to the Middle Ages with the introduction of Trivium and Quadrivium, with the modern ages, a Copernican twist is added in the teaching and it becomes more focused in the development of reason as opposed to just instruction. None the less, the fundamental end is not lost, it’s in every moment the formation of an integral, ethical, critical, human who is also compromised with analyzing reality.   However,  the present of the University of Costa Rica, along with other superior education institutions is that they are now receiving students from Generation Z. This are students that are highly influenced by image, globalization, immediacy and technology. The previous elements imply new challenges in humanistic education, therefore the importance of philosophy of education as a discipline that can illuminate new roads of critical thinking in the task of humanities